Randomized controlled clinical trial evaluating multiplex polymerase chain reaction for pathogen identification and therapy adaptation in critical care patients with pulmonary or abdominal sepsis. (June 2015) - Tafelski, Sascha; Nachtigall, Irit; Adam, Thomas; Bereswill, Stefan; Faust, Jana; Tamarkin, Andrey; Trefzer, Tanja; Deja, Maria; Idelevich, Evgeny A; Wernecke, Klaus-Dieter; Becker, Karsten; Spies, Claudia
Objective: To determine whether a multiplex polymerase chain reaction (PCR)-based test could reduce the time required for initial pathogen identification in patients in an intensive care unit (ICU) setting. Methods: This double-blind, parallel-group randomized controlled trial** enrolled adults with suspected pulmonary or abdominal sepsis caused by an unknown pathogen. Both the intervention and control groups underwent the standard blood culture (BC) testing, but additional pathogen identification, based on the results of a LightCycler® SeptiFast PCR test, were provided in the intervention group. Results: The study enrolled 37 patients in the control group and 41 in the intervention group. Baseline clinical and demographic characteristics were similar in both groups. The PCR-based test identified a pathogen in 10 out of 41 (24.4%) patients in the intervention group, with a mean duration from sampling to providing the information to the ICU of 15.9 h. In the control group, BC results were available after a significantly longer period (38.1 h). Conclusion: The LightCycler® SeptiFast PCR test demonstrated a significant reduction in the time required for initial pathogen identification, compared with standard BC.